Brain cancer after radiation exposure from CT examinations of children and young adults: results from the EPI-CT cohort study. Issue 1 (January 2023) - Hauptmann, Michael; Byrnes, Graham; Cardis, Elisabeth; Bernier, Marie-Odile; Blettner, Maria; Dabin, Jérémie; Engels, Hilde; Istad, Tore S; Johansen, Christoffer; Kaijser, Magnus; Kjaerheim, Kristina; Journy, Neige; et al.
Summary: Background: The European EPI-CT study aims to quantify cancer risks from CT examinations of children and young adults. Here, we assess the risk of brain cancer. Methods: We pooled data from nine European countries for this cohort study. Eligible participants had at least one CT examination before age 22 years documented between 1977 and 2014, had no previous diagnosis of cancer or benign brain tumour, and were alive and cancer-free at least 5 years after the first CT. Participants were identified through the Radiology Information System in 276 hospitals. Participants were linked with national or regional registries of cancer and vital status, and eligible cases were patients with brain cancers according to WHO International Classification of Diseases for Oncology. Gliomas were analysed separately to all brain cancers. Organ doses were reconstructed using historical machine settings and a large sample of CT images. Excess relative risks (ERRs) of brain cancer per 100 mGy of cumulative brain dose were calculated with linear dose-response modelling. The outcome was the first reported diagnosis of brain cancer after an exclusion period of 5 years after the first electronically recorded CT examination. Findings: We identified 948 174 individuals, of whom 658 752 (69%) were eligible for our study. 368 721 (56%) of 658 752 participants were male and 290 031 (44%) were female. During a median follow-up of 5·6 years (IQR 2·4–10·1), 165 brain cancers occurred, including 121 (73%) gliomas. Mean cumulative brain dose, lagged by 5 years, was 47·4 mGy (SD 60·9) among all individuals and 76·0 mGy (100·1) among people with brain cancer. A significant linear dose-response relationship was observed for all brain cancers (ERR per 100 mGy 1·27 [95% CI 0·51–2·69]) and for gliomas separately (ERR per 100 mGy 1·11 [0·36–2·59]). Results were robust when the start of follow-up was delayed beyond 5 years and when participants with possibly previously unreported cancers were excluded. Interpretation: The observed significant dose-response relationship between CT-related radiation exposure and brain cancer in this large, multicentre study with individual dose evaluation emphasises careful justification of paediatric CTs and use of doses as low as reasonably possible. Funding: EU FP7; Belgian Cancer Registry; La Ligue contre le Cancer, L'Institut National du Cancer, France; Ministry of Health, Labour and Welfare of Japan; German Federal Ministry of Education and Research; Worldwide Cancer Research; Dutch Cancer Society; Research Council of Norway; Consejo de Seguridad Nuclear, Generalitat de Catalunya, Spain; US National Cancer Institute; UK National Institute for Health Research; Public Health England.